Combined search for the Standard Model Higgs boson using up to 4.9 fb-1 of pp collision data at s=7TeV with the ATLAS detector at the LHC - Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; et al. (2012)
A combined search for the Standard Model Higgs boson with the ATLAS experiment at the LHC using datasets corresponding to integrated luminosities from 1.04 fb-1 to 4.9 fb-1 of pp collisions collected at s=7TeV is presented. The Higgs boson mass ranges 112.9-115.5 GeV, 131-238 GeV and 251-466 GeV are excluded at the 95% confidence level (CL), while the range 124-519 GeV is expected to be excluded in the absence of a signal. An excess of events is observed around mH~126GeV with a local significance of 3.5 standard deviations (σ). The local significances of H→γγ, H→ZZ(z.ast;)→ℓ+ℓ-ℓ'+ℓ'- and H→WW(z.ast;)→ℓ+νℓ'-ν- the three most sensitive channels in this mass range, are 2.8σ, 2.1σ and 1.4σ, respectively. The global probability for the background to produce such a fluctuation anywhere in the explored Higgs boson mass range 110-600 GeV is estimated to be ~1.4% or, equivalently, 2.2σ. © 2012 CERN.